COVID-19 in patients with paracoccidioidomycosis. - Priscila Marques de Macedo; Lorena Macedo Pestana Benko; Eduardo Mastrangelo Marinho Falcão; Joshua D Nosanchuk; Rodrigo Almeida-Paes; Antonio Carlos Francesconi do Valle (Public Library of Science (PLoS), 2023)
Introduction In 2020, we reported the first patient with concomitant COVID-19 and paracoccidioidomycosis (PCM). Since then, no other cases have been recorded in the literature. We aim to update information on the occurrence of COVID-19 in patients with PCM followed at a reference center for infectious diseases at Rio de Janeiro, Brazil. Methods We reviewed the medical records from patients diagnosed with PCM who presented with clinical symptoms, radiological findings, and/or laboratory diagnosis of COVID-19 at any time during their acute or follow-up care. The clinical profiles of these patients were described. Results Between March 2020 and September 2022, we identified six individuals with COVID-19 among the 117 patients with PCM evaluated. The median age was 38 years and the male to female ratio 2:1. Most patients (n = 5) presented for evaluation due to acute PCM. The severity of COVID-19 ranged from mild to severe in acute PCM and only the single patient with chronic PCM died. Conclusions There is a range of disease severity in COVID-19 and PCM co-infection and concomitant disease may represent a severe association, especially in the chronic type of the mycosis with pulmonary involvement. As COVID-19 and chronic PCM share similar clinical aspects and PCM is neglected, it is probable that COVID-19 has been hampering simultaneous PCM diagnosis, which can explain the absence of new co-infection reports. With the continued persistence of COVID-19 globally, these findings further suggest that more attention by providers is necessary to identify co-infections with Paracoccidioides.